Non-invasive electron paramagnetic resonance imaging detects tumor redox imbalance induced by ferroptosis - Kazuhiro Kato; Hironobu Yasui; Hideo Sato-Akaba; Miho C. Emoto; Hirotada G. Fujii; Maciej M. Kmiec; Periannan Kuppusamy; Masaki Nagane; Tadashi Yamashita; Osamu Inanami (Redox Report)
Targeting ferroptosis, cell death caused by the iron-dependent accumulation of lipid peroxides, and disruption of the redox balance are promising strategies in cancer therapy owing to the physiological characteristics of cancer cells. However, the detection of ferroptosis using in vivo imaging remains challenging. We previously reported that redox maps showing the reduction power per unit time of implanted tumor tissues via non-invasive redox imaging using a novel, compact, and portable electron paramagnetic resonance imaging (EPRI) device could be compared with tumor tissue sections. This study aimed to apply the EPRI technique to the in vivo detection of ferroptosis. Notably, redox maps reflecting changes in the redox status of tumors induced by the ferroptosis-inducing agent imidazole ketone erastin (IKE) were compared with the immunohistochemical images of 4-hydroxynonenal (4-HNE) in tumor tissue sections. Our comparison revealed a negative correlation between the reducing power of tumor tissue and the number of 4-HNE-positive cells. Furthermore, the control and IKE-treated groups exhibited significantly different distributions on the correlation map. Therefore, redox imaging using EPRI may contribute to the non-invasive detection of ferroptosis in vivo.